Avaliação da influência da precipitação de fases intermetálicas na resistência à corrosão do aço inoxidável superferrítico - Pereira, Ursula Cid (2019)
Superferritic steels are characterized by high chromium content (exceeding 25 wt%) and also have molybdenum in their composition. Meantime, superferritic stainless steels were developed for use in heat exchangers and marine environments. The high concentration of alloying elements in the superferritic stainless steels can affect the microstructural stability causing the precipitation of intermetallic phases, such as sigma (σ), chi (χ) and alpha line (α '). In order to understand how the precipitation of intermetallic phases influences in the corrosion resistance of superferritic steels, thus experimental alloys have been developed: Fe-25% Cr-XMo-YNi (X = 5 and 7%, Y = 2 and 4%). Heat treatments for 15 min, 1 h, 10 h, and 100 h at temperatures of 600oC, 700°C, 800°C and 900°C were performed and the results obtained were compared with the solubilized samples. Microstructural characterization of the samples and analysis of the precipitates were attained by optical microscopy and scanning electron microscopy equipped with energy dispersive spectrometry. The corrosion resistance was evaluated by linear cyclic polarization, electrochemical impedance spectroscopy, chronoamperometry and critical pitting temperature techniques. The solution of 3.5% NaCl was used as electrolyte and tests were realized in triplicate. Results showed that the 7Mo4Ni alloy presented better performance in corrosion resistance compared to other samples treated at the same time (100 h) and samples treated with 15 min, 1 h and 10 h the 7Mo2Ni alloy presented better performance in corrosion resistance.